Creativity across the primary curriculum : framing and developing practice - Craft, Anna. (London : New York : Routledge, 2000)
Creativity will be covered by the new National Curriculum in 2000/2001. This book takes an inspirational look at how to foster children's creativity as well as following the guidelines in the National Curriculum
Includes bibliographical references and index.
Keywords: Creative thinking -- Study and teaching -- Great Britain